2013
DOI: 10.1002/cbdv.201200231
|View full text |Cite
|
Sign up to set email alerts
|

11α‐Ethoxy‐β‐boswellic Acid and Nizwanone, a New Boswellic Acid Derivative and a New Triterpene, Respectively, from Boswellia sacra

Abstract: A new boswellic acid derivative, 11α-ethoxy-β-boswellic acid (EBA; 1) and a new ursane-type triterpene, named nizwanone (2), were isolated from Omani frankincense Boswellia sacra Flueck. together with two known compounds papyriogenin B and rigidenol. The structures of 1 and 2 were elucidated by detailed spectroscopic analysis using (1) H- and (13) C-NMR, (1) H,(1) H-COSY, HMQC, HMBC, and HR-EI-MS techniques. The relative configurations of 1 and 2 were assigned by comparative analysis of the NMR spectral data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…12 ), which were isolated from Boswellia spp. for the fi rst time (Al-Harrasi et al 2013 ). (Fattorusso et al 1983 ;Klein and Obermann 1978 ;Basar et al 2001 ;Hamm et al 2005 ;Hanuš et al 2007 ) Table 1 The main terpenes identifi ed in Boswellia sacra E -β-ocimene (32.3 %) Sabinene (5.2 %) β-pinene 1.8 %) Myrcene (6.9 %) α-pinene (5.3 %) Limonene (33.5 %) γ-terpinene (1.0 %) E -caryophyllene (0.9 %) Al-Harrasi and Al-Saidi ( 2008 ) Boswellia sacra Boswellia carterii α-thujene (0.6 %) α-thujene (7.9 %) α-pinene (68.2 %) α-pinene (37.3 %) Camphene (2.1 %) Camphene (0.8 %) Sabinene (2.9 %) Sabinene (4.9 %) β-pinene (2.0 %) β-pinene (1.8 %) Myrcene (0.7 %) Myrcene (7.3 %) Limonene + β-phellandrene …”
Section: Chemical Constituents and Bioactive Compounds Of Myrrhmentioning
confidence: 99%
“…12 ), which were isolated from Boswellia spp. for the fi rst time (Al-Harrasi et al 2013 ). (Fattorusso et al 1983 ;Klein and Obermann 1978 ;Basar et al 2001 ;Hamm et al 2005 ;Hanuš et al 2007 ) Table 1 The main terpenes identifi ed in Boswellia sacra E -β-ocimene (32.3 %) Sabinene (5.2 %) β-pinene 1.8 %) Myrcene (6.9 %) α-pinene (5.3 %) Limonene (33.5 %) γ-terpinene (1.0 %) E -caryophyllene (0.9 %) Al-Harrasi and Al-Saidi ( 2008 ) Boswellia sacra Boswellia carterii α-thujene (0.6 %) α-thujene (7.9 %) α-pinene (68.2 %) α-pinene (37.3 %) Camphene (2.1 %) Camphene (0.8 %) Sabinene (2.9 %) Sabinene (4.9 %) β-pinene (2.0 %) β-pinene (1.8 %) Myrcene (0.7 %) Myrcene (7.3 %) Limonene + β-phellandrene …”
Section: Chemical Constituents and Bioactive Compounds Of Myrrhmentioning
confidence: 99%
“…The nine known compounds were identified as populeuphroid L ( 5 ) [7], epimansumbinol ( 6 ) [12], ergosta-4,6,8(15),22-tetraen-3-one ( 7 ) [15], mansumbin-13(17)-en-3,16-dione ( 8 ) [16], 3 α -acetoxy-mansumbin-13(17)-en-16-one ( 9 ) [17], 3-epi-δ-amyrin ( 10 ) [18], α-boswellic acid ( 11 ) [19], 11α-ethoxy-β-boswellic acid ( 12 ) [20], acetyl-11-keto-β-boswellic acid ( 13 ) [21] by a comparison of their spectroscopic data with those reported in the literature. Although compound 12 is a known one, it might be an artefact produced during extraction procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, boscartin M, isoincensole oxide, incensole oxide, and incensole oxide acetate had a mild hepatoprotective effect at 10 μM [25]. In the other report by Wang et al, the investigation of B. sacra led to the isolation of ten new cembrane-type diterpenes, including boscartins AL-AU (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and five known analogs (35)(36)(37)(38)(39). Moreover, biological evaluations revealed that compounds 27, 29, 36, and 37 displayed hepatoprotective activities against paracetamol-induced HepG2 cell damage at 10 μM.…”
Section: Diterpenoidsmentioning
confidence: 97%
“…Compounds 70 and 71 were evaluated for their antiproliferative activity against MDA-MB-231 breast cancer cells, and it was observed that these pyrolysate products were able to inhibit cancer cell growth [31]. A new ursane-type triterpene, namely, nizwanone (72) was reported from Omani frankincense B. sacra Flueck along with two known compounds papyriogenin B (73) and rigidenol (74) by Al-Harrasi et al [32]. 11-ketoursolic acid (75), 3α-hydroxy-8, 24-dien-tirucallic acid (76), 3-O-acetyl-oleanolic acid (77), and 3-O-acetyl-ursulic acid (78) were reported as triterpenoid compounds from a methanolic extract [33].…”
Section: Diterpenoidsmentioning
confidence: 99%